Hypokalemia-Induced Arrhythmias and Heart Failure: New Insights and Implications for Therapy - Skogestad, Jonas; Aronsen, Jan Magnus (Frontiers in Physiology, 2018)
Routine use of diuretics and neurohumoral activation make hypokalemia (serum K+ < 3. 5 mM) a prevalent electrolyte disorder among heart failure patients, contributing to the increased risk of ventricular arrhythmias and sudden cardiac death in heart failure. Recent experimental studies have suggested that hypokalemia-induced arrhythmias are initiated by the reduced activity of the Na+/K+-ATPase (NKA), subsequently leading to Ca2+ overload, Ca2+/Calmodulin-dependent kinase II (CaMKII) activation, and development of afterdepolarizations. In this article, we review the current mechanistic evidence of hypokalemia-induced triggered arrhythmias and discuss how molecular changes in heart failure might lower the threshold for these arrhythmias. Finally, we discuss how recent insights into hypokalemia-induced arrhythmias could have potential implications for future antiarrhythmic treatment strategies.